A nomogram based on CHADS2 score for predicting atrial fibrillation recurrence after cryoballoon ablation. Issue 12 (9th November 2022) - Liu, Yu; Tian, Youpeng; Fan, Jinqi; Xu, Yanping; Chen, Yun‐Lin; Yin, Yuehui
Abstract: Background: As reported, CHADS2 scoring system moderately predicts the atrial fibrillation (AF) recurrence, a common event after cryoballoon ablation. We aimed to improve the diagnostic accuracy of the CHADS2 score by adding several routine auxiliary detection indicators into the scoring system and constructing a CHADS2 score‐based nomogram to predict AF recurrence in patients with paroxysmal AF undergoing cryoballoon ablation. Methods: Eighty‐four patients with paroxysmal AF undergoing cryoballoon ablation were enrolled. Baseline characteristics were collected. The multivariable Cox proportional hazards model was used to identify the significantly related predictors of recurrence and to construct the nomogram whose performance was evaluated by the discrimination and calibration tests. Results: Thirty‐five patients developed AF recurrence after a mean follow up of 19.0 ± 15.77 months. In the Cox multivariate model, CHADS2 (>2) (hazard ratio [HR]: 2.38; 95% confidence interval [CI]: 1.14–4.98, p = .021) and albumin‐to‐globulin ratio (AGR) (HR: 2.49; 95% CI: 1.26–4.92, p < .008) were independent risk factors associated with AF recurrence. In addition to CHADS2, AGR and red blood cell distribution width were used to construct the nomogram. As a result, the discrimination of the concordance index for the predictive model of AF recurrence was increased from 0.56 (95% CI: 0.494–0.632) to 0.712 (95% CI: 0.631–0.811). The 24‐month one well matched the ideal 45° line among the calibration plots for 6, 12, and 24 months' recurrence‐free survival. Conclusion: This novel easy‐to‐use CHADS2 score‐based nomogram may be used to predict AF recurrence for patient of paroxysmal AF undergoing cryoballoon ablation. Further external validation is still needed.